Optimization of speckle pattern based on integer programming method. (October 2020) - Xu, Xiangyang; Ren, Xiangyun; Zhong, Fuqiang; Quan, Chenggen; He, Xiaoyuan
Highlights: A mathematical model for finding the subset with the largest sum of square of subset intensity gradients is established. The optimized speckle patterns for digital image correlation are produced with the integer programming method. Both the simulations and experiments show that the proposed optimized speckle patterns have a stronger anti-nose ability than random patterns. Abstract: The performance of digital image correlation (DIC) method heavily depends on the quality of the speckle pattern. Extensive studies have been conducted to evaluate the speckle pattern, in order to reduce the errors of DIC. It is generally understood that the sum of square of subset intensity gradients (SSSIG) is the most relevant metric to the accuracy of the DIC; and the higher SSSIG indicates the better quality of the speckle pattern. However, there are few works on the optimization of the speckle pattern. In this work, we propose an integer programming method (IPM) to obtain the subset having the highest SSSIG. The speckle pattern derived from the proposed IPM has a relatively high SSSIG and has a strong anti-noise capability. The regular patterns (e.g. checkerboard-type) can also be avoided by the proposed method. Both the simulation and experiment have been conducted to validate the effectiveness of the proposed method. The simulation results show that the standard deviation (STD) of the displacements obtained by using the proposed speckle pattern in this study is reduced by 25.2% and 10.7%, respectively, comparing with the results obtained by the conventional random speckle pattern and the optimized speckle pattern in our earlier work. In addition, the experimental results from a tensile testing also agreed to the results from the simulation.